Impacto econômico do reconhecimento extrajudicial de paternidade socioafetiva - Assad, Michele Matias Malheiro (2023)
The relevant facts of human existence cannot be left to the discretion of remembrance or certified by any of the common ways. In this context, the Civil Registry of Natural Persons presents itself as a delegated institution able to faithfully and safely record the significant events and links of the biography of individuals, especially the paternal branch liame. The joint work of doctrine, jurisprudence, General Justice Affairs of the federative units and the National Council of Justice made the registrability of socioaffective affiliation a reality in Brazil. Aiming to regulate uniformly the procedure of extrajudicial recognition of socioaffective paternity, the General Internal Affairs Of Justice of the CNJ, in November 2017, issued Provision no. 63, amended in August 2019, by Provision no. 83. The displacement of activities attributed to the Judiciary to the scope of extrajudicial services, in addition to reducing the number of lawsuits related to civil registration, favors a huge contingent of people throughout the national territory, generating savings to public coffers. To make up this dissertation, the hypothetical-deductive method was used, aided by the statistical method.